Il moderno : Descartes, Spinoza, Leibniz - Cassier, Ernst (Krinein, 2022)
This volume offers an insight into the relationship between Ernst Cassirer and modern philosophy through the comparison with three emblematic figures of the philosophical horizon of the seventeenth-century: Descartes, Spinoza and Leibniz. This Cassirerian itinerary in the "spirit of the modern" is traced through the collection of three texts of Cassirer's production, two of which are translated into Italian for the first time. In these writings the author deals with the philosophical impact of Descartes' teaching on Queen Christina of Sweden, with the analysis of Spinoza's notion of nature and with Leibniz's Discourse on Metaphysics. The three texts represent some of the most brilliant and insightful research that would lead the author to the development of the philosophy of culture.